2020
DOI: 10.7554/elife.60647
|View full text |Cite
|
Sign up to set email alerts
|

Light-regulated allosteric switch enables temporal and subcellular control of enzyme activity

Abstract: Engineered allosteric regulation of protein activity provides significant advantages for the development of robust and broadly applicable tools. However, the application of allosteric switches in optogenetics has been scarce and suffers from critical limitations. Here, we report an optogenetic approach that utilizes an engineered Light-Regulated (LightR) allosteric switch module to achieve tight spatiotemporal control of enzymatic activity. Using the tyrosine kinase Src as a model, we demonstrate efficient reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 111 publications
0
35
0
Order By: Relevance
“…In natural proteins, domain insertions and rearrangements play a key role in generating regulatory diversity, with kinases serving as a prototypical example [8][9][10][11]. In engineered proteins, domain insertions have been used to generate fluorescent metabolite biosensors [7], sugar-regulated TEM-1 -lactamase variants [12], and a myriad of light controlled proteins including kinases, ion channels, guanosine triphosphatases, guanine exchange factors, and Cas9 variants [5,[13][14][15][16][17][18]. In all cases, domain insertion provides a powerful means to confer new regulation in a modular fashion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In natural proteins, domain insertions and rearrangements play a key role in generating regulatory diversity, with kinases serving as a prototypical example [8][9][10][11]. In engineered proteins, domain insertions have been used to generate fluorescent metabolite biosensors [7], sugar-regulated TEM-1 -lactamase variants [12], and a myriad of light controlled proteins including kinases, ion channels, guanosine triphosphatases, guanine exchange factors, and Cas9 variants [5,[13][14][15][16][17][18]. In all cases, domain insertion provides a powerful means to confer new regulation in a modular fashion.…”
Section: Introductionmentioning
confidence: 99%
“…In natural proteins, domain insertions and rearrangements play a key role in generating regulatory diversity, with kinases serving as a prototypical example ( Fan et al, 2018 ; Huse and Kuriyan, 2002 ; Peisajovich et al, 2010 ; Shah et al, 2018 ). In engineered proteins, domain insertions have been used to generate fluorescent metabolite biosensors ( Nadler et al, 2016 ), sugar-regulated TEM-1 β-lactamase variants ( Guntas et al, 2005 ), and a myriad of light-controlled proteins including kinases, ion channels, guanosine triphosphatases, guanine exchange factors, and Cas9 variants ( Dagliyan et al, 2016 ; Wang et al, 2016 ; Karginov et al, 2011 ; Toettcher et al, 2013 ; Shaaya et al, 2020 ; Coyote-Maestas et al, 2019 ; Richter et al, 2016 ). In all cases, domain insertion provides a powerful means to confer new regulation in a modular fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent work has demonstrated that such functionality can also be engineered. For instance, to control the activity of certain protein kinases by light, an engineered light-sensitive domain, pdDronpa 20 , the small photo-switchable domain LOV2 (Light, Oxygen and Voltage protein domain 2) 21 , or the recent Light-Regulated domain engineered from Vivid photoreceptor 22 , were integrated into the kinase in a manner, such that light altered its activity. The same was recently also accomplished for the metabolic enzymes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In natural proteins, domain insertions and rearrangements play a key role in generating regulatory diversity, with kinases serving as a prototypical example [8][9][10][11]. In engineered proteins, domain insertions have been used to generate fluorescent metabolite biosensors [7], sugar-regulated TEM-1 b-lactamase variants [12], and a myriad of light controlled proteins including kinases, ion channels, guanosine triphosphatases, guanine exchange factors, and Cas9 variants [5,[13][14][15][16][17][18]. In all cases, domain insertion provides a powerful means to confer new regulation in a modular fashion.…”
Section: Introductionmentioning
confidence: 99%